Pengaruh Latihan Push Up Dengan Kaki Di Atas Bangku Terhadap Hasil Servis Atas Permainan Bola Voli Pada Siswa Kelas X Di SMA Negeri 3 Palembang - Perabu Nita; Wiranto (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This study aims to determine the effect of push-ups with feet on a bench on top service ability in volleyball games for class X IPS students at SMA Negeri 3 Palembang. This research is an experimental research with one group pretest-posttest design. The sample in this study amounted to 25 students, the data were processed using statistical formulas in the form of calculating the average, standard deviation, and two-mean test. The analysis in this study used the t-test formula at a significant level of 5%. The results obtained were that there was an effect of push-up training with legs on the bench on the upper service ability in volleyball games in class X IPS at SMA Negeri 3 Palembang, p. This can be proven based on the t test data analysis, the results obtained tcount = 2.495> ttable = 1.71. Therefore, according to the predetermined hypothesis testing criteria, it can be concluded that Ha is accepted and Ho is rejected because there is a significant effect of the push up exercise with the legs above. bench against the Ability of Top Service in Volleyball Games for Class X IPS Students at SMA Negeri 3 Palembang